FLASHBACK FINANCE: DEVELOPING A STRATEGY FOR BUSINESS SUSTAINABILITY - Yofi Syarkani; Alfiana; Abdul Munim Al Basmeleh (Adisam Publisher, 2024)
A business continuity strategy is a collection of organizational objectives, guidelines, plans, and initiatives with the goal of spotting market possibilities, maintaining the company, and generating revenue. Business sustainability strategy is part of business strategy and cannot be separated from the business model. To grow the business sustainably, companies must continue to evaluate their business strategies. Business strategy analysis is an important step in designing a viable business model, so that it has a lasting impact on business life. Businesses should have appropriate financial strategies and management to face changes in tough business strategies. Effective communication between the finance department and other departments is crucial for the implementation of financial management initiatives. To meet shared financial objectives, all departments within the firm must collaborate. Businesses may enhance performance, preserve financial stability, and guarantee long-term sustainability by putting suitable financial management techniques into practice. This research discusses the definition and principles of sustainability in a business context, financial approaches to maintaining and improving business sustainability, details of strategies adopted by businesses to ensure their sustainability, and a discussion of key findings that show the relationship between historical financial analysis and the development of sustainability strategies.